Rancang Bangun Sistem Informasi Penjualan Barang Di Toko Radina Project Berbasis Website - Akar, Rutmeida Handayani; Widiatry, Widiatry (Universitas Palangka Raya, 2021)
Radina Project store is a clothing store located in the city of Palangka Raya. The Radina Project store uses the Instagram platform as a media for selling goods, to purchase goods through Instagram, people must contact the owner's contact first to get information on the desired item, then have to wait for the owner's response to get the required information. Based on the problems above, this website was designed which aims to increase effectiveness, provide information that facilitates transaction services and assist people in getting information about the desired goods more quickly and simplifying the ordering process. This Website-Based Information System for Sales of Goods at Radina Project Store is designed and built using the Waterfall method with the stages of analysis, design, coding, testing and support or maintenance. System testing is done by using the black box testing method (Blackbox testing). The final result obtained is a website-based goods sales information system. This system is able to provide information that facilitates transaction services and is able to provide information on Radina Project store goods to users so that users get convenience, especially in getting information on goods and simplify the ordering process.